Metode Pendidikan Bhagawan Domya Sebagai Upaya Membentuk Siswa Berkarakter - Ni Nyoman Sudiani; Kadek Hemamalini; I Wayan Saklit (Jayapangus Press, 2022)
This research aims to examine the educational methods applied by Bhagavan Domya in order to realize students with character. President Joko Widodo's work program outlined in Nawa Cita is to prioritize character education for the nation's generation so that character education gets more priority, namely 70 percent for elementary education level and 60 percent at the high school level, rather than the teaching and learning process for subject matter. But in reality, there is currently a deterioration in student character. The decline in student character can be allegedly because the method to educate the character of students today is not appropriate. This research is qualitative descriptive research using discourse analysis methods. The discourse analyzed is the story of Bhagavan Domya in the book Adi Parva Chapter III sloka 1 to 11 and the type of research data is written data. Discourse analysis is used to find out the educational methods hidden in the text of Bhagavan Domya's story. Data collection is done through watch and recording. The results showed that the educational period developed by Bhagavan Domya is a method of assignment, supervision, testing, appreciation and advising. The method of education proved effective in forming the character of the three students, such as the character of devotion to the teacher, hard work, responsibility, religious, tough, willing to sacrifice, caring for the environment, honesty and independent, so that the three students were given the gift of knowledge that is useful for life.